Does MRI add value in selecting patients for thrombectomy beyond the 6 h window? A matched-control analysis - Cheng, Huiran; Yu, Zequan; Ma, Gaoting; Wang, Anxin; Jia, Baixue; Tong, Xu; Ma, Ning; Gao, Feng; Mo, Dapeng; Song, Ligang; Xuan, Sun; Huo, Xiaochuan; et al. (Frontiers in Neurology, 2023)
Background Controversy exists regarding the need of advanced imaging for patient selection in the extended window. Aims To analyze the effect of initial imaging modalities on clinical outcomes of patients underwent MT in the extended window. Methods This was a retrospective analysis of a prospective registry, the Endovascular Treatment Key Technique and Emergency Workflow Improvement of Acute Ischemic Stroke (ANGEL-ACT) registry which was conducted at 111 hospitals between November 2017 and March 2019 in China. Primary study cohort and Guideline like cohort were identified, in each cohort, two imaging modalities for patient selection in 6 to 24 h window were defined: (1) NCCT ± CTA, (2) MRI. Guideline-like cohort were further screened based on key features of the DAWN and DEFUSE 3 trials. The primary outcome was 90 day mRS. The safety outcomes were sICH, any ICH and 90-day mortality. Results After adjusting for covariates, there were no significant differences in 90 day mRS or any safety outcomes between two imaging modalities groups in both cohorts. All outcome measures of mixed-effects logistic regression model were consistent with propensity score matching model. Conclusion Our results indicate that patients presented with anterior large vessel occlusion in the extended time window can potentially benefit from MT even in the absence of MRI selection. This conclusion needs to be verified by the prospective randomized clinical trials.